2013
DOI: 10.1002/acp.2918
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Memory for Newspaper Advertisements: Effects of Ad–Editorial Congruency and Location

Abstract: SummaryPrevious research suggests that the same ad can have different effects depending upon the media context in which the ad appears. This experiment investigated how the semantic relation between the content of advertisements and editorial texts, and the ad location on newspaper pages affect attention and memory for advertisements. We recorded participants' eye movements while they read newspaper articles to rate how interesting the texts were. Recognition for ads, logos, and editorial headlines was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 51 publications
4
38
0
1
Order By: Relevance
“…As a result, processing the text requires less attention for the overall message to be comprehended. 11 Longer dwell time on the text in incongruent PWLs might also be due to alternating attention between the image and the text in order to produce a complete mental model of the overall message. 32 Independent of condition, smokers focused faster and longer on the image than on the text, suggesting that images in PWLs capture and hold smokers attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, processing the text requires less attention for the overall message to be comprehended. 11 Longer dwell time on the text in incongruent PWLs might also be due to alternating attention between the image and the text in order to produce a complete mental model of the overall message. 32 Independent of condition, smokers focused faster and longer on the image than on the text, suggesting that images in PWLs capture and hold smokers attention.…”
Section: Discussionmentioning
confidence: 99%
“…10 Previous research has shown that ads were recalled better when their semantic content was congruent with the editorial material. [11][12][13][14] However, although one study found that congruency had no effect on attention to the ads, 13 another study 11 found that incongruent ads were viewed longer than congruent ads. Semantic priming, 15 which has been shown to influence processing fluency, 16 has been proposed as a theoretical explanation for memory effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embedding an ad into a thematically congruent programme could also foster a semantic prime of the programme content in processing the ad. This prime could act as a facilitator, increasing the accessibility of the primed content, in this case the ad, and facilitate its processing (Simola, Kivikangas, Kuisma, & Krause, 2013). The use of the editorial context or other ads as a semantic prime has been shown to produce better memory for thematically congruent ads (Finlay, Marmurek, & Morton, 2005;Simola, et al, 2013), to improve ad attitude and brand evaluations (Shen & Chen, 2007) and also to improve brand attitudes and purchase intentions (Shen & Chen, 2007;Yi, 1990aYi, , 1990bYi, , 1993.…”
mentioning
confidence: 99%
“…Appropriately, Simola et al (2013) stated that "the same ad… can have different effects depending upon the context in which the ad appears. "…”
Section: Frequency Of Word Playmentioning
confidence: 99%